Consumer Behavior towards Cosmetics Products in Kathmandu Valley - Bharat Rai,; Rewan Kumar Dahal,; Binod Ghimire, (Pravaha, 2022)
The article's primary goal is to look at the factors affecting consumers' behavior in buying cosmetics items in Kathmandu Valley. The study examines how one's physical attractiveness might make one feel good about oneself. Most women who use cosmetics are female. In the Kathmandu valley, the demand for cosmetics items is rising quickly. The dependent variable in this study is consumer behavior, and the independent variables are quality, price, personal factors, and loyalty which substantially impact consumer behavior. This study made use of primary data. Using a structured questionnaire and a convenient sampling technique, information was gathered from 189 customers who purchased cosmetics in Kathmandu valley. Valid conclusions were reached using descriptive factor analysis, correlation, and multiple regression analysis. Exploratory factor analysis was done to find the commonalities and composite reliability. The outcome demonstrated that consumer behavior is significantly influenced by product quality, price, and personal characteristics. But it was discovered that loyalty does not significantly influence consumer purchasing behavior toward cosmetic products in the Kathmandu Valley.